Adult Ventricular Septal Defect Repair Using a Robotic Totally Endoscopic Approach: A Case Report. Issue 4 (July 2020) - Mirzai, Saeid; Hibino, Narutoshi; Torregrossa, Gianluca; Balkhy, Husam H.
The growth and advancement of minimally invasive cardiac surgery in recent years has allowed robotic and totally endoscopic procedures to become safe and effective options for the treatment of patients with various diseases of the heart. However, despite these advances, outcome data for robotic correction of congenital cardiac anomalies are scarce. This is particularly true for robotic ventricular septal defect (VSD) repair with initial experiences only recently having been published by a single group. Here, we present the case of a 29-year-old female who underwent robotic totally endoscopic VSD repair due to persistent symptoms with resolution of preoperative shunting and severe tricuspid regurgitation following surgery. This unique case adds to the limited data currently available in the literature on robotic VSD repair to show that it is a safe procedure when performed by a dedicated surgical team experienced in minimally invasive robotic cardiac surgery. We feel that, in this setting, the benefits of a robotic surgical approach can be afforded to more patients with excellent results.